Pragmatic consciousness-rising activities and EFL learners' speech act performance of 'making suggestion' - Abolfathiasl, Hossein; Abdullah, Ain Nadzimah (Academy Publisher, 2015)
The present study examined the impact of pragmatic consciousness-raising activities on EFL learners’ immediate and delayed performance of suggestions, using a pretest, treatment, posttest design. Two intact classes consisting of 52 Iranian intermediate EFL learners during an intensive English course were assigned as an experimental group with 27 learners and a control group with 25 learners. A Written Discourse Completion Test (WDCT) was given to both groups prior to the intervention that revealed no significant difference between the groups’ pragmatic performance. The experimental group then underwent an eight-week pragmatic consciousness-raising treatment on the pragmalinguistic and sociopragmatic features of performing suggestions. After the completion of the intervention, a posttest and, after eight weeks, a delayed posttest was given to both groups to examine the effectiveness of the PCR intervention. The analyses of the scores of the groups revealed that first, the treatment was effective on the EFL learners’ pragmatic performance and second, the treatment significantly enhanced the experimental group’s ability to produce appropriate suggestions. Also, the study showed that the trend of structure and strategy use by learners in the treatment group changed as a result of the PCR treatment from the pretest to posttest and delayed posttest conditions. This study showed that consciousness-raising at the metapragmatic level improved EFL learners’ pragmatic performance and variety of form-strategy use substantially; thus, it should be taken more seriously in L2 instruction and material development.